2018
DOI: 10.1080/02670844.2017.1381375
|View full text |Cite
|
Sign up to set email alerts
|

Developing of galling during the forming and its improvement by physical vapour depositing

Abstract: In sheet metal stamping, galling is initiated and developed aggressively at the mould radius, where sheet metal undergoes large plastic deformation. This study sheds light on correlating the level of sheet plastic deformation with galling initiation on the mould surface. The 3D topography facilitated the observation of galling evolution process on the surface of quenched/tempered mould. The observation on the sliding sheet counterpart showed that with larger plastic deformation, zinc-coated surface tended to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The surface quality was categorized into machined surface roughness (R a ), material deposition roughness (R b ) and machined cum deposition roughness (R ab ). Ra rises as the current increases because it produces more intense sparks [34], which create cracks and craters on the machined surface, lowering the quality of the machined surface. In the case of R b and R ab , the best surface quality was attained when machined at the current of 30 A, and with further increase worsens the surface quality owing to plasma densification.…”
Section: Resultsmentioning
confidence: 99%
“…The surface quality was categorized into machined surface roughness (R a ), material deposition roughness (R b ) and machined cum deposition roughness (R ab ). Ra rises as the current increases because it produces more intense sparks [34], which create cracks and craters on the machined surface, lowering the quality of the machined surface. In the case of R b and R ab , the best surface quality was attained when machined at the current of 30 A, and with further increase worsens the surface quality owing to plasma densification.…”
Section: Resultsmentioning
confidence: 99%
“…During whole manufacturing process, the tool design has a significant role in the initiation of galling and it is highly vulnerable to the surface roughness of tool (without coating) rather than surface irregularities of the sheet [31]. Zhou et al [32], Yangui et al [33] and Dong et al [27] in this context researchers had reported that the commencement and progression of galling originates at the mould radius (i.e. around 0° to 70°) during forming process during which there is a severe plastic deformation of sheet metal, inducing adhesion of sheet material to the surface of the tool and hence galling occurs.…”
Section: Pothole In Design Of Sheet Metal Forming Contributing Gallingmentioning
confidence: 99%
“…In order to be able to predict the value of coefficient of friction (COF) in analyses of sheet-forming processes, it is necessary to carry out the tribological test for a given pair of mating elements (tool and plate) [8]. The COF is mainly influenced by the roughness of the tool and of the material formed, lubrication conditions [9], mechanical properties of the sheet metal [10], character of contact (static/dynamic) [11] and temperature [12].…”
Section: Introductionmentioning
confidence: 99%